(3GdUMGM aj GddZIs - (3ESeGYjd Hf MeGO GdLhgQj , CHh fUQ, J (B393 (3g` s ((3SYO Hf Ydi Hf CHj SYO GdLGSJi s)
(3ChdgG (B:s
(3jHOC HaUd GdOGd s
(3BNQgG (B:s
(3jfJgi HaUd GdjGA s
(3GdfSNI HgG MhGTs
(3GdfUa GdKGfis
(3Je fSNI ef fSNI HNW GHf GdNTGH efbhdI ef fSNI GdCUd GdeUMMI HNW GdgQhis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs